PENERAPAN METODE PEMBELAJARAN PEMODELAN PADA MATA PELAJARAN SENI BUDAYA KELAS VIII 5 DI SMP NEGERI 10 PADANG - Ahsani Arasy; Esy Maestro; Harisnal Hadi (SENDRATASIK UNP, 2018)
Abstract This article aimed to reveal the impact of the application of the learning method of modelling the learning results of students on basic competencies to playing traditional musical instruments in groups and in class VIII 5 SMP Negeri 10 Padang. This research used Classroom Action Research. The object of research was the students of class VIII5 who studied the arts and culture lessons. This classroom action research was done through 2 cycles; they were cycle 1 and cycle 2. Data collection in this research data used some techniques that were observation and test result learn. The data processing procedures were done by data selection and percentage of data. The results showed that the application of modeling learning method on the subject of art and culture (music) could improve student learning outcomes. This was in accordance with student learning outcomes in pre-cycle; cycle 1 and cycle 2 were increased. The use of modeling learning methods could improve student learning outcomes in the subjects of art and culture (music) in class VIII 5 SMP Negeri 10 Padang. Thus,  it could be concluded that this research was successful. Keywords: Application, Learning Modeling Method, Cultural Art